Effect of Adding L-carnitine and Probiotic on Performance and Carcass Parameters of Broiler Chickens - Cyril Hrnčár; Martin Gašparovič; Emília Hanusová; Anton Hanus; Veronika Pistová; Henrieta Arpášová; Martin Fik; Jozef Bujko; Jozef Gašparík (Scientific Papers Animal Science and Biotechnologies, 2023)
The study was realised to investigate the effects of adding L-carnitine and probiotic on performance and carcass parameters of broiler chickens. Totally 240 one-day old broiler Ross 308 chickens randomly divided into four groups. Control group with basal diet without supplementation, experimental group 1 with probiotic in feed mixture in dose of 7.5 g/kg; experimental group 2 with L-carnitine in dose of 1ml/1.2 l in drinking water and experimental group 3 with probiotic in feed mixture in dose of 7.5 g/ kg + L-carnitine in drinking water in dose of 1 ml/1.2 l in drinking water. The results of this study indicated that supplementation with L-carnitine and probiotic statistically increased (p<0.05) final body weight of broiler chickens in comparison to other groups. The other results showed no significant differences  (p>0.05) in feed consumption among groups in 42 days of age and broiler chickens receiving L-carnitine + probiotic had lowest mortality compared to the other groups. Furthermore, diet supplementation with L-carnitine and probiotic slightly increased (p>0.05) breast proportion of broiler chickens at the expense of a slight reduction (p>0.05) of thighs proportion in recognized statistically no significant differences (p>0.05). Further result showed statistically decreased weight of abdominal fat in broiler chickens with L-carnitine and probiotic and no significant effect in weight of giblets and carcass yield between control and other groups.